CHEMICAL COMPOSITION OF THE SNAILS OF BARKGONG Strombus luhuanus FROM SULI WATERS, CENTRAL MALUKU - Absalom Luturmas; Maureen M. Pattinasarany; La Ode Alirman Afu (Aquaculture Department, University of Mataram, 2022)
Strombus luhuanus is a gastropod that is commonly found in Maluku and is very popular with the local community because it has a high nutritional content. Lives in colonies and is abundant in shallow intertidal and subtidal areas at a depth of about 20 m. The aim of the study was to determine the composition of proximate, amino acids and fatty acids that have the potential as bioactive compounds in the field of pharmacology. The results of the proximate study of fresh meat of Strombus luhuanus contained 79.78% water content, 0.89%, ash 15.64% protein, 0.96% fat, 2.73% carbohydrates. Amino acids found included glutamic acid, aspartic acid, leucine, arginine, lysine, glycine, alanine, threonine, valine, serine, isoleucine, proline, phenylalanine, tyrosine, cystine, methionine, histidine and tryptophan. Fatty acids consist of saturated fatty acids and unsaturated fatty acids.